The Role of ZnO as a Dopant and an Intergranular Phase in the Electrical Properties of Ca0.6Sr0.4TiO3 Ceramics - Zhang, Lin; Wang, Qian; Li, Jie; Wang, Chuanhui (Frontiers in Energy Research, 2021)
ZnO was introduced into Ca0.6Sr0.4TiO3 ceramics as a dopant and an intergrangular phase in this research, followed by detailed structure characterization, energy storage performance analysis, and electrical behavior studies. The results revealed that the existence of ZnO as a dopant led to the decrease of conduction activation energy and the deterioration of energy storage behavior, while appropriate introduction of ZnO as an intergranular phase resulted in the increase of conduction activation energy and the optimization of energy storage performance. Additionally, the inverse relation between interfacial polarization and energy storage performance was observed in this study. Finally, an increased energy storage density of 1.16 J/cm3 was achieved in 1 mol% ZnO-added Ca0.6Sr0.4TiO3 ceramics.